2014
DOI: 10.1186/1755-7682-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Low hepatitis B vaccine uptake among surgical residents in Cameroon

Abstract: BackgroundHepatitis B virus (HBV) infection is one of the most serious occupational hazards faced by healthcare workers. Surgical personnel are particularly at risk. HBV infection is preventable by vaccination, but no previous study has assessed HBV vaccination coverage among healthcare workers in Cameroon. We assessed knowledge of risk factors of HBV infection, awareness of HBV vaccine, and vaccination status of surgical residents in Cameroon.MethodsA structured pretested questionnaire was administered to 49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
3
15
2
Order By: Relevance
“…Preventive vaccination against hepatitis B for hospital staff is standard in many countries, but is still not implemented in many resources-poor settings [ 10 , 11 ]. There have been reports of weak immune responses to HBV vaccination caused by, for example, diabetes or a current viral infection [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preventive vaccination against hepatitis B for hospital staff is standard in many countries, but is still not implemented in many resources-poor settings [ 10 , 11 ]. There have been reports of weak immune responses to HBV vaccination caused by, for example, diabetes or a current viral infection [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, vaccination coverage of medical students in Cameroon was 18%; however, only 10% of the fully vaccinated students had their antibody levels checked. 20,21 In this study, of the few who had been vaccinated, some did not finish the full vaccine series; and none of the HCWs who did finish the full dosage series, had an antibody titre to confirm immunity, which is recommended by WHO. A study in Karachi reported a high vaccination coverage of 81.8%, 22 however, the study population's level of immunity was not confirmed with an HBsAg titre.…”
Section: Discussionmentioning
confidence: 91%
“…Another explanation, which is consistent with other studies, is that long occupational exposurenumber of years of employmentincrease chances for HBV acquisition. 14,20 To date, Tanzania has not performed a controlled and monitored nationwide vaccination campaign among highrisk groups, such as HCWs, as recommended by WHO. 16 Very few HCWs have been vaccinated because vaccinations were only given as a donation or as a precondition for clinical research work.…”
Section: Discussionmentioning
confidence: 99%
“…The main finding in these papers was that PEP was underused, and it was speculated that this was partly due to the low level of PEP-related knowledge. Forty-eight questions were about different types of vaccines; 23 on hepatitis B [39][40][41][42][43], eight on human papilloma virus [44][45][46], three on influenza [47,48] viruses, and 14 questions on adverse events following immunization [49]. Questions were about overall awareness of different types of vaccines, and the effectiveness, what comprised a dose/full course, how long the vaccines offered protection, and about the safety of vaccination, adverse reactions after immunization, and medication used to prevent/relieve vaccinationrelated immune reaction.…”
Section: Disease Focusmentioning
confidence: 99%